HYBRID LEARNING SEBAGAI ALTERNATIF MODEL PEMBELAJARAN TEMATIK DI KELAS 2 SEKOLAH DASAR PADA MASA PANDEMI - Mustika, Rika; Nurhasanah, Ana; Adya Pribadi, Reksa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This study aims to describe the hybrid learning teaching model which is an alternative thematic teaching model in grade 2 SD. This research is a qualitative descriptive study. For data collection in this study, it will be done by taking secondary data in the form of interviews to support the literature review that has been collected by researchers. The stages of the research carried out were data collection in the form of interviews, articles, data reduction, and data review. This study shows the results of interviews with teachers who have knowledge of how well students learn online, and the disadvantages that face-to-face and virtual learning must bear simultaneously but still produce effective results for learning. Other results from proponents suggest that now, educators, administrators, and K-12 families and other education sectors can see the impact of hybrid teaching delivery options, all of which make teaching more effective.